If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = -2(-3 + -1y) 7 = (-3 * -2 + -1y * -2) 7 = (6 + 2y) Solving 7 = 6 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 7 + -2y = 6 + 2y + -2y Combine like terms: 2y + -2y = 0 7 + -2y = 6 + 0 7 + -2y = 6 Add '-7' to each side of the equation. 7 + -7 + -2y = 6 + -7 Combine like terms: 7 + -7 = 0 0 + -2y = 6 + -7 -2y = 6 + -7 Combine like terms: 6 + -7 = -1 -2y = -1 Divide each side by '-2'. y = 0.5 Simplifying y = 0.5
| 5+2y=15 | | -3(n+2)=12 | | 2(4-3m)=13 | | 3(5+2x)=8(5+x) | | 64-4x=32x+24 | | 5(x-6)=-15 | | (6t-1)+(4t+2)+(7t+3)+3t=124 | | 4y^3-2=1y-8y^2 | | 6x+10=-120-7x | | 5(2+3+x)=110 | | 2y+10=2y+5 | | 2j(7j^2+jk^2+5k)-9k(-2j^2k^2+2k^2+3j)=0 | | t-4=21 | | t-4=24 | | 2.5x+1.5x=6 | | 15x^3-12x^2+3x= | | -20=-4+z | | -20=-4+7 | | 3x-50=1 | | 6+1x-10x^2=0 | | 7x-50=1 | | -10=-n+2-2n | | -14x^3-7x^2= | | 3x*27723355675= | | (x-6)7=49 | | 3x*2= | | 12=2x-7x-8 | | 9x^2+6x-1=0 | | 62-4x=14x+18 | | 3x*2=9 | | 10x^2+29x+10=0 | | 10x^2+29x+10=0 |